2009
DOI: 10.1521/pedi.2009.23.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Social Consequences of Borderline Personality Disorder Symptoms in a Population-Based Survey: Marital Distress, Marital Violence, and Marital Disruption

Abstract: Associations between borderline personality disorder (BPD) symptoms and marital distress, perpetration of marital violence, and marital dissolution were evaluated in a population-based sample of married adults. The incremental association between BPD symptom severity and marital outcomes was also examined, controlling for the presence of Axis I disorders. Respondents from the National Comorbidity Survey Replication (NCS-R) who had been married at least once completed measures of BPD symptoms and provided infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 2 publications
5
66
1
5
Order By: Relevance
“…In another sample of college students (n = 225; 140 females), the severity of BPD traits was related to mate retention tactics [111], i.e., jealousy induction in women and emotional manipulation in men. In a population-based sample of married adults (n = 1,127; 635 females), BPD symptom severity was positively associated with marital distress, perpetration of minor and severe marital violence, and marital disruption even after controlling for the presence of 12-month axis I disorders [112]. Similarly, individuals with high levels of BPD traits experienced more negative daily interpersonal events than individuals with low levels of BPD traits [113,114].…”
Section: Impaired Intimacymentioning
confidence: 99%
“…In another sample of college students (n = 225; 140 females), the severity of BPD traits was related to mate retention tactics [111], i.e., jealousy induction in women and emotional manipulation in men. In a population-based sample of married adults (n = 1,127; 635 females), BPD symptom severity was positively associated with marital distress, perpetration of minor and severe marital violence, and marital disruption even after controlling for the presence of 12-month axis I disorders [112]. Similarly, individuals with high levels of BPD traits experienced more negative daily interpersonal events than individuals with low levels of BPD traits [113,114].…”
Section: Impaired Intimacymentioning
confidence: 99%
“…Consistent with this view, a number of studies suggest that subclinical manifestations of borderline personality are associated with impairments in functioning among those not seeking psychiatric treatment. Findings cover several diverse domains of functioning, such as marital and romantic relationships (Daley, Burge, & Hammen, 2000;Hill et al, 2011;Selby, Braithwaite, Joiner, & Fincham, 2008;Whisman & Schonbrun, 2009), employment (Sansone, Leung, & Wiederman, 2012Sansone & Wiederman, 2013), physical health (Powers & Oltmanns, 2012), and academic, interpersonal, and social pursuits (Bagge et al, 2004;Oltmanns, Melley, & Turkheimer, 2002;Powers, Gleason, & Oltmanns, 2013).…”
mentioning
confidence: 99%
“…Several studies of people with BPD have shown that clinical relapses or emotional crises tend to be triggered by interpersonal events such as conflicts and quarrels or periods of rapid break-up and reconciliation [44][45][46][47][48][49] . Ultimately, these emotional crises are responsible for a large proportion of psychiatric emergencies and inpatient care, resulting in a direct economic cost of up to EUR 13,000 per year [4,50] .…”
mentioning
confidence: 99%